Physiotherapy students’ and teachers’ perception of assessment - Cáceres Bermón, Zoraya Trinidad; Munévar Ramírez, Olga Jeannette; Lara Gómez, Luisa Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This study was inspired in educational reflection, especially the assessment process. Teachers’ and students’ conceptions of assessment influence the teaching and learning process. Such concepts are based in theoretical positions involving certain educational models and, therefore, assessment paradigms. The aim was to unveil physiotherapy teachers’ and students’ conceptions of assessment at the University of Pamplona and their impact on clinical practice. A qualitative approach based on the phenomenological method was used. Data were collected through a question guide developed during interviews and through the observation of students’ and supervising teachers’ assessment practice in the second level of physiotherapy clinical practices at the University of Pamplona. Grounded theory was used for analysis and interpretation of information. According to the results, teachers and students see assessment as a regulating element that allows for a specific observation of accomplishment of activities related to the context where clinical practices are developed. Decision-making is identified and students’ progress, performances, and skills are highlighted